Changes In Biochemical Components Of Rice Following Naa Application - Jahan, Nargis; Golam Adam, AMM (Journal of the Asiatic Society of Bangladesh, Science, 2014)
An investigation on the effect of Naphthalene acetic acid (NAA) on the changes of biochemical components of two varieties of rice (Oryza sativa L.), BRR1 dhan 29 and BRRI dhan 50 was carried out. Two concentrations of NAA, 100 and 200 ppm were used as foliar spray. In BRRI dhan 29, significant increases in chlorophyll a and chlorophyll b contents of leaf were observed due to both the treatments at the flowering stage, whereas, carotenoids at the grain filling stage only. But in BRRI dhan 50, the total leaf pigments decreased at the flowering and grain filling stage, but was significant in case of chlorophyll a at the flowering stage. Significant increases in protein content of leaf were recorded at the tillering and flowering stage of BRRI dhan 29 following 100 ppm NAA treatment. In BRRI dhan 50, the only significant increase was recorded at grain filling stage due to 200 ppm NAA treatment. In both the varieties carbohydrates, protein, fat, and energy content of grain increased due to both the treatments and the maximum increase in all the cases was recorded due to 100 ppm NAA treatment. Ash and moisture content of grain reduced following both the treatments in both the varieties, the maximum reduction was due to 100 ppm NAA treatment Asiat. Soc. Bangladesh, Sci. 40(2): 173-178, December 2014